Monitoring the Dough Properties, Quality Characteristics and Volatile Compounds of Whole Wheat Bread Made by Different Sourdough Types during Frozen Storage - Ozulku, Gorkem (MDPI, 2024)
There is a need to increase the consumption of whole wheat bread (WWB) due to its health benefits by overcoming its poor technological quality and improving its sensory characteristics. In this study, sourdough bread-making and frozen dough technology were combined to provide fresh WWB at any time with better quality. Also, it was aimed to investigate the effects of three types of sourdough (type I, II, and IV) on the final quality of WWB during frozen storage (-30 degrees C, 14 and 28 days). The tan delta of WWB with type I sourdough was highest at the end of the frozen storage. Freezable water content was lower on day 0 for WWB with type II and IV sourdough than other bread types. No significant effect of frozen storage was observed in bread types in terms of an alpha helix structure, except for WWB with type I sourdough. A lower hardness increment was shown in WWB with baker's yeast and WWB with type II sourdough over 14 days of frozen storage when compared to other bread types. WWB with type I sourdough and WWB with type IV sourdough were differentiated from other bread samples in volatile compound (VC) analysis on frozen storage days 28 and 0, respectively. The frozen storage of WWB with baker's yeast and WWB with type II sourdough caused no notable changes in the VCs profile. These results suggest that a less detrimental effect of frozen storage was observed in WWB with type II sourdough, indicating a more favorable choice for producing WWB with sourdough.
Keywords: dough rheology; freezable water content; secondary structure; HS/GC-MS analyses; RHEOLOGICAL BEHAVIOR; FERMENTATION; GLUTEN; FLOUR; IMPACT; BRAN; TIME; Food Science & Technology